2019
DOI: 10.1101/2019.12.20.884320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Horizontal gene transfer of thepirABgenes responsible for Acute Hepatopancreatic Necrosis Disease (AHPND) turns a non-Vibriostrain into an AHPND-positive pathogen

Abstract: In the past decade, shrimp farms, particularly those established in Asia, Mexico and South America suffered from the outbreak of an emergent penaeid shrimp disease known as Acute Hepatopancreatic Necrosis Disease (AHNPD). The PirA and PirB toxins produced by plasmid pVA1 in Vibrio parahaemolyticus were reported to cause the AHPND pathology. More recent research demonstrated that V. parahaemolyticus is not the only species that can cause AHPND, as other Vibrio species were also found to contain PirAB-containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Further, cross species HGT of toxin genes has been demonstrated by Muthukrishnan et al (2019) through co-culture experiments of pirAB positive V. parahaemolyticus isolates and pirAB negative Algoriphagus sp. Strain.…”
Section: Dynamics Of Toxin-linked Mgesmentioning
confidence: 85%
“…Further, cross species HGT of toxin genes has been demonstrated by Muthukrishnan et al (2019) through co-culture experiments of pirAB positive V. parahaemolyticus isolates and pirAB negative Algoriphagus sp. Strain.…”
Section: Dynamics Of Toxin-linked Mgesmentioning
confidence: 85%
“…According to reports on the PirA/B toxin genes present in pVA1, V. parahaemolyticus strains lacking PirA/B fail to cause AHPND; however, the strains transformed with plasmids containing PirA/B have been found to show clinical signs of AHPND and cause 100% mortality in shrimp larvae (Muthukrishnan, Defoirdt, Ina‐Salwany, et al., 2019; Muthukrishnan, Defoirdt, Shariff, et al., 2019; Tinwongger et al., 2016). Additionally, pVA1 can be transferred among similar clusters and is capable of self‐transfer using the pndA PSK gene system, which is a mobilizing gene associated with conjugative transfer (Lee et al., 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The isolated HJ‐2023 strain was confirmed to be V. campbellii via gene sequence identification, but the same result was not obtained in the bacterial identification based on the biochemical characteristics determined using the API tests, as the information on V. campbellii was not registered in the bacterial identification reading software; therefore, it was likely confirmed as a similar Vibrio species. Because of this diversity in biochemical characteristics, when bacteria are isolated from diseased white‐leg shrimp using TCBS medium, approximately 84.3% of them form green colonies (Muthukrishnan, Defoirdt, Ina‐Salwany, et al., 2019; Muthukrishnan, Defoirdt, Shariff, et al., 2019). V. campbellii also forms green colonies because it lacks a sucrose hydrolase gene, making it difficult to distinguish it from V. parahaemolyticus (Dong, Bi, Wang, et al., 2017; Dong, Wang, Xie, et al., 2017; Dong, Wang, Zou, et al., 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another report confirmed that pVA1 pirAB vp genes could be transferred from an AHPND-causing V. parahaemolyticus to a non- Vibrio and non-pathogenic Algoriphagus sp. [ 25 ]. These developments suggest that pVA1-related plasmids could be transmitted between different species, which would make it more difficult to control AHPND.…”
Section: The Ahpnd-causing Plasmid Pva1mentioning
confidence: 99%